2004
DOI: 10.1103/physrevb.69.104533
|View full text |Cite
|
Sign up to set email alerts
|

Vortex dynamics at subcritical currents at microwave frequencies inDyBa2Cu3O

Abstract: We have investigated the dynamics of vortices at subcritical microwave currents in dc magnetic fields ͑up to 0.8 T͒ in epitaxial DyBa 2 Cu 3 O 7Ϫ␦ ͑DBCO͒ thin films. Microwave measurements were performed using microstrip resonators as test vehicles at 4.88 GHz and 9.55 GHz on laser ablated DBCO thin films in the thickness range 1800-3800 Å. Experimental evidence indicates that the peak effect ͑PE͒ observed in surface resistance vs temperature (R s vs T) plots in applied dc magnetic fields up to 0.8 T is primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…its thickness d and width 2w. As it is seen from figure 1(A), the most pronounced peaks in the curve P dis (S 0 ) are located in the region of tens of S 0 ; thus, only if the dimensions of a resonator lie in the range corresponding to 5 ≤ S 0 ≤ (20 − 30) for the rather low frequency, the multi-peak picture similar to the ones obtained in [6,7,8] can be experimentally observed.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…its thickness d and width 2w. As it is seen from figure 1(A), the most pronounced peaks in the curve P dis (S 0 ) are located in the region of tens of S 0 ; thus, only if the dimensions of a resonator lie in the range corresponding to 5 ≤ S 0 ≤ (20 − 30) for the rather low frequency, the multi-peak picture similar to the ones obtained in [6,7,8] can be experimentally observed.…”
Section: Discussionsupporting
confidence: 60%
“…In the current report the theoretical model of the linear response of HTS thin films with trapped vortices developed in [9] is used to model the dc magnetic field and the temperature dependence of energy losses P dis (B, T ) connected with the oscillation of Abrikosov vortices in thin SC films cooled down in (FC) and without (ZFC) external dc magnetic field. It is shown that, under the general assumptions on the magnetic field and temperature behavior of J c , α L and η, the quasi-periodic form of P dis (T ) dependence neatly corresponds to the ones obtained in [6,7,8]. By varying the shape of J c (B, T ), α L (B, T ) and η(B, T ) dependences, the conditions for the appearance of nonmonotonic parts on P dis (B, T ) curve is also clarified.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…In this case, the change in the response due to the application of the magnetic field is due to the vortex motion: superfluid and quasiparticle contributions give a nearly field-independent contribution that can be easily subtracted out. Moreover, we assume the superconducting material to be a thin film, a sample geometry widely used in microwave experiments [3,19,31,53,54,59]. In these conditions it can be shown 1 that ρ v , being essentially proportional to the surface impedance tensor, can be taken as the actually measured quantity.…”
Section: Application To Experiments: the Measured Complex Vortex Resi...mentioning
confidence: 99%